Peran Komunikasi dalam Administrasi Pendidikan untuk Meningkatkan Efektivitas Pengelolaan Institusi Pendidikan - Rochaeni, Reni; Khoerulbariyyah, Farah Budiarti; Wulandari, Baiduri; Suyatman, Ujang (BISMA : Business and Management Journal, 2024)
Communication plays an important role in educational administration, particularly in building coordination, resolving conflicts, and achieving institutional goals. This article aims to examine the role of effective communication in education administration through a literature review approach. The results of the study show that open, directed, and value-based communication can improve the efficiency of educational institution management, strengthen the relationship between leaders and staff, and increase stakeholder satisfaction. This article also highlights communication barriers in education administration and offers recommendations to overcome them.ini bertujuan untuk mengkaji peran komunikasi yang efektif dalam administrasi pendidikan melalui pendekatan kajian literatur. Hasil kajian menunjukkan bahwa komunikasi yang terbuka, terarah, dan berbasis nilai dapat meningkatkan efisiensi pengelolaan lembaga pendidikan, mempererat hubungan antara pemimpin dan staf, serta meningkatkan kepuasan stakeholder. Artikel ini juga menyoroti kendala komunikasi dalam administrasi pendidikan dan menawarkan rekomendasi untuk mengatasinya